PEMBIAYAAN EKSTERNAL, MANAJEMEN LABA DAN FINANCIAL DEVELOPMENT: BUKTI EMPIRIS DARI ENAM NEGARA DI ASIA - Daniel Y. Titapasanea (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2021)
The inconsistency of previous research findings motivated this study to examine the effect of external financing on earnings management using two financing components simultaneously. This study also examines the effect of financial development on the relationship between external financing and earnings management.The research samples are manufacturing companies from Indonesia, Japan, Singapore, South Korea, Malaysia and India. The total sample of companies used was 1,191 companies (5,128 observations). External financing is measured by the amount of changes in debt and equity. Earnings management is measured using the modified Jones model while financial development is measured using index numbers released by the World Economic Forum.The results of the study prove that there is a significant negative effect between external financing and earnings management. However, there is no evidence that the effect of external financing on earnings management is stronger in countries with large financial development index numbers than in countries with small index numbers. Keywords: Debt Financing, Equity Financing, Profit Management, Financial Development.